Concept Of Ahara With Respect To Prakriti :A Review - Gupta, Preeti Kumari; Yadav, Sarika (International Research Journal of Ayurveda & Yoga, 2020)
In Ayurveda system of medicine ,the whole concept of health and disease, prevention and management is based on type of constitution and it is rooted through Tridosha theory of Ayurveda. Thus Ayurveda is only applied science which is still in practice having unbroken continuity. Dietetics can be defined as the branch of knowledge concerned with Diet & its effects on health .According to WHO the enjoyment of the highest attainable standard of health is one of the fundamental rights of every human being. Ayurveda the “Science of life” is a system of medicine that utilizes various therapies including diet ,herbal preprations and yoga to restore harmony balance within the body. It focuses more on the healthy living and well being. One of the main goals of Ayurveda is to maintain health of a healthy individual and to attain the health in the diseased. Diet is mentioned in 3 sub – pillar (sub tripods of life), since it is responsible is for growth & development of the human body. One of the important concepts in Ayurveda is “Prakriti ”the innate nature of an individual & is determined at the time of conception itself & remains throughout the life. Knowing of Prakriti helps in maintaining the health and preventing the disease. Ayurveda prescribes various foods and lifestyles According to one’s Prakriti and suggests that one should follow these guidelines to prevent various disorders and to promote health. In this era of lifestyle disorders in order to improve the quality of life & to bring down the cost of health care one should know about his Prakriti & the diet suitable for his body constitution .Here by this paper is intended to explain the concepts of diet in Ayurveda in a backlight of Prakriti.